Nutritional and sensory implications of pig tripe as ingredient in fresh pork sausage production - Worlah Yawo Akwetey; Justice Bless Dorleku (International Journal of Agricultural Research, Innovation and Technology, 2026)
This experiment was conducted to study the possibility of using pig tripe for producing fresh pork sausages. Three types of sausages, each weighing 2 kg, were produced using pig tripe or without pig tripe. A consumer panel used a 9-point hedonic scale to assess the sensory characteristics of sausages. All the sensory characteristics evaluated showed no significant (p>0.05) differences across treatments. The contents of fat significantly reduced (p<0.05) when pig tripe was increased in formulating the sausages (T1=36.32%, T2=33.14% and T3=29.90%) and protein contents ranged from 27.55% (T1) to 22.90 (T3). Increasing levels of pig tripe resulted in the reduction of protein contents, but protein in T1 was not different from T2. The observed differences in ash and moisture composition of fried sausages were not significantly different. These findings suggest that pig tripe is a viable offal in the production of fresh pork sausage. It was concluded that 34% pig tripe could be used as an ingredient in producing fresh pork sausages without compromising sensory attributes and protein contents, but with reduced fat contents. Int. J. Agril. Res. Innov. Tech. 15(2): 25-29, Dec 2025